2003
DOI: 10.1007/s00246-002-0328-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Compliance and Practice of Antibiotic Endocarditis Prophylaxis of Patients with Congenital Heart Disease

Abstract: The aim of this study was to determine the knowledge, compliance, and practice of antibiotic endocarditis prophylaxis (AEP) for patients with congenital heart disease (CHD) during various diagnostic or therapeutic procedures. Patients (296) and their parents were interrogated during a visit with an 18-question survey pertaining to the practice of AEP. Most patients (91.6%) had acyanotic congenital heart disease, usually preoperative (45.3%), or had high risk of infective endocarditis due to previous endocardit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
7
1
5
Order By: Relevance
“…Many studies conducted in several centers have shown that parental knowledge of the care needed to prevent IE in children with heart disease is lower than expected [9][10][11]13,15,16]. In the present study, only 34% of parents/ caregivers have demonstrated satisfactory knowledge, and only 15 respondents seemed to know what IE was.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Many studies conducted in several centers have shown that parental knowledge of the care needed to prevent IE in children with heart disease is lower than expected [9][10][11]13,15,16]. In the present study, only 34% of parents/ caregivers have demonstrated satisfactory knowledge, and only 15 respondents seemed to know what IE was.…”
Section: Discussioncontrasting
confidence: 72%
“…Several studies indicate that parents' knowledge about their children's heart problems is inadequate, as well as the necessary precautions to prevent EI [9][10][11][12][13]. The Brazilian Society of Cardiology has no guidelines for IE prophylaxis and the various departments of pediatric cardiology embraced the AHA recommendations by 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Amoxicillin prophylaxis reduces bacteremia in children after dental procedures from 84% to 33% [85]. Prophylaxis, however, may fail due to patient-related factors (compliance) in up to 40%, physician-related factors (knowledge) in 50%, and ineffective drugs against rare pathogens in 66% [33,38,42,65,68,69,72,73,83,84,88,97,108,116,119,122,137]. Nowadays, bacteremia from daily care activities is judged a far greater risk [134].…”
Section: Sources Of Bacteremiamentioning
confidence: 99%
“…Invasive dental procedures have often been regarded as the main cause of infective endocarditis (IE). The prevention of IE has been debated and has remained controversial in the dental profession 1–4 . There is an ongoing debate 5–7 about which dental procedures warrant antibiotic prophylaxis (AP).…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of IE has been debated and has remained controversial in the dental profession. [1][2][3][4] There is an ongoing debate 5-7 about which dental procedures warrant antibiotic prophylaxis (AP). The latest recommendations stress using AP prior to dental procedures associated with significant bleeding in patients with high and moderate risk of endocarditis.…”
Section: Introductionmentioning
confidence: 99%